Synthesis of electroless Ni catalyst supported on SBA‐15 for hydrogen and carbon production by catalytic decomposition of methane. (28th September 2020) - Chen, Qianqian; Lua, Aik Chong
Summary: Electroless plating was used to prepare nickel particles as catalysts to generate hydrogen by methane decomposition. Nickel particles were supported on SBA‐15 mesoporous silica structures which have good mechanical strength and are thermally stable. Ag particles were first prepared and attached on the support surface as seeds for the Ni particles. Electroless nickel plating provides a uniform deposition of Ni particles on the Ag/support surface and produces varying loadings of nickel deposits. These favorable features of the combined electroless nickel plating and catalyst support are a good catalyst candidate for thermal decomposition of methane. The results showed medium interaction of the catalyst with the support and exposed a higher nickel loading on the support surface. The activity of the catalysts was investigated under two temperature‐programmed processes involving a constant temperature mode and a stepwise heating temperature mode. The Ni/SBA‐15 catalyst was characterized using ion chromatography, transmission electron microscopy, X‐ray diffraction, and hydrogen temperature‐programmed reduction. The performance of the catalyst was dependent on the catalyst loading and reaction temperature. The 32 wt% Ni/SBA‐15 catalyst exhibited the best catalytic performance with a stable methane conversion of 0.44 at 575°C. The 32 wt% Ni/SBA‐15 catalyst also withstood the highest resistance to deactivation. The results of this study demonstrated the feasibility of using electroless nickel plating technique for the preparation of catalyst for the catalytic methane decomposition reaction. Abstract : Experimental results on hydrogen production by thermocatalytic decomposition of methane using a catalyst prepared by electroless nickel plating on Ag/SBA‐15 support were reported. The Ni/SBA‐15 with Ag seeds is a novel catalyst for thermal decomposition of methane and has not been reported by other researchers. Methane conversion of Ni/SBA‐15 catalysts at different reaction temperatures and various percentages of Ni content were studied. TEM micrographs of 26 wt% Ni/SBA‐15 and 32 wt% Ni/SBA‐15 catalysts (top) and their catalytic activities under different reaction temperatures (bottom).